Germanium terminated (1 0 0) diamond. (27th February 2017) - Sear, Michael J; Schenk, Alex K; Tadich, Anton; Spencer, Benjamin J; Wright, Christopher A; Stacey, Alastair; Pakes, Chris I
Abstract: An ordered germanium terminated (1 0 0) diamond surface has been formed and characterised using a combination of low energy electron diffraction and synchrotron-based core level photoemission spectroscopy. A number of preparation methods are explored, in each case inducing a two domain ( 3 × 1 ) surface reconstruction. The surface becomes saturated with bonded germanium such that each ( 3 × 1 ) unit cell hosts 1.26 Ge atoms on average, and possesses a negative electron affinity of −0.71 eV.